Answer:
6x^3 - 2x^2 -11x +4
Step-by-step explanation:
(3x-4)(2x^2+2x-1)
Multiply 3x by the second term
3x* (2x^2+2x-1)
6x^3 +6x^2 -3x
Multiply -4 by the second term
-4*(2x^2+2x-1)
-8x^2 -8x+4
Add these together, lining up the terms
6x^3 +6x^2 -3x
-8x^2 -8x+4
----------------------------------
6x^3 - 2x^2 -11x +4
Answer:
a 95
b 932
c 50
d 131
Step-by-step explanation:
formula (C × 9/5) + 32 = F
Answer:
B, D
Step-by-step explanation:
-3(0.15 - 0.2 +0.25p) = -3(-0.05 +0.25p) = 0.15-0.75p
A doesn't work because -3(0.15 - 0.2 +0.25p) = -0.45+0.6-0.75
C doesn't work because 3(0.15+0.2+0.25p) = 0.45+0.6+0.75 which doesn't equal -0.45+0.6-0.75.
E doesn't work because 0.15-0.2 = -0.05 not 0.05.
The answer is C) (1,7)and (7,1). In order to find the correct answer ,just substitute the numbers for x and y in the problem,so:5(1)(7)+9=44 .35+9 =44,44=44 ,so that's true .Then check the other set of given numbers by substituting for x and y :5(7)(1)+9=44,35*1=35+9= 44,therefore 44=44 ,so both sides are true.*Also remember x is always the first number given,and then y.*